2013
DOI: 10.1371/journal.pone.0081914
|View full text |Cite|
|
Sign up to set email alerts
|

FABP4 Induces Vascular Smooth Muscle Cell Proliferation and Migration through a MAPK-Dependent Pathway

Abstract: PurposeThe migration and proliferation of vascular smooth muscle cells play crucial roles in the development of atherosclerotic lesions. This study examined the effects of fatty acid binding protein 4 (FABP4), an adipokine that is associated with cardiovascular risk, endothelial dysfunction and proinflammatory effects, on the migration and proliferation of human coronary artery smooth muscle cells (HCASMCs). Methods and ResultsA DNA 5-bromo-2′-deoxy-uridine (BrdU) incorporation assay indicated that FABP4 signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…B1 repetitive elements are the sequences of short interspersed nucleotide elements in mice, corresponding to the Alu sequence in humans (19). Increasing evidence suggests that B1 repetitive element hypomethylation is associated with gene transcriptional activity in the pathogenesis of cardiovascular diseases, particularly AS (43). In the present study, it was also found that B1 repetitive elements exhibited hypomethylation in the blood cells of the AS model.…”
Section: Discussionsupporting
confidence: 65%
“…B1 repetitive elements are the sequences of short interspersed nucleotide elements in mice, corresponding to the Alu sequence in humans (19). Increasing evidence suggests that B1 repetitive element hypomethylation is associated with gene transcriptional activity in the pathogenesis of cardiovascular diseases, particularly AS (43). In the present study, it was also found that B1 repetitive elements exhibited hypomethylation in the blood cells of the AS model.…”
Section: Discussionsupporting
confidence: 65%
“…Although the biological role of FABP4 is not fully understood, it has been linked to insulin sensitivity, lipid metabolism, and inflammation [46]. Previously, we have shown that FABP4 levels are elevated in obese and diabetic individuals, and such increased levels are closely correlated with adverse lipid profiles, insulin resistance, and vascular smooth muscle cell proliferation [47,48,49,50]. In this study, protein and mRNA expression of FABP4 were reduced in OR and TH mice, which suggests alleviation of fat accumulation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous administration of FABP4 was able to induce smooth muscle cell proliferation and chemokinesis in vitro [38]. Therefore we considered the possibility that circulating FABP4 could contribute to pathological retinal neovascularization.…”
Section: Discussionmentioning
confidence: 99%